A proposed vision for the role of Saudi universities in developing and enhancing the intellectual security of their students - Asiri, Aisha Ali Msoud (Journal of Educational and Psychological Sciences, 2024)
The research aimed to present a proposed vision for the role of Saudi universities in developing and enhancing intellectual security among their students. To achieve this, the research used the inductive descriptive method, based on which a proposed vision for the role of Saudi universities in developing and enhancing intellectual security among students was presented by clarifying the contributions required from university administrations. , the role of student activities, the role of university faculty members, as well as the role of educational curricula in universities. The research ended with a number of recommendations; Including: (Intensifying efforts to develop university students’ skills in the ability to criticize, analyze, judge information, and make decisions; by adding a critical thinking course to their study plans, and intensifying efforts to help university students use multiple sources to obtain knowledge and acquire learning skills. Self-learning and continuous learning, and investing in university activities and events in clarifying the concept of security in general, and intellectual security in particular, and giving space for the student to actively participate in this aspect).
Keywords: proposed vision; intellectual security; Saudi universities